2002
DOI: 10.1073/pnas.032665099
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of multiple signaling pathways in CD40-regulated gene expression in B lymphocytes

Abstract: CD40͞CD40L interaction is essential for multiple biological events in T dependent humoral immune responses, including B cell survival and proliferation, germinal center and memory B cell formation, and antibody isotype switching and affinity maturation. By using high-density microarrays, we examined gene expression in primary mouse B lymphocytes after multiple time points of CD40L stimulation. In addition to genes involved in cell survival and growth, which are also induced by other mitogens such as lipopolysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 57 publications
5
96
0
3
Order By: Relevance
“…Pharmacological inhibition of any of these pathways dramatically reduces the proliferation response induced by CD40 stimulation [37]. However, our data suggest that activation of these MAP kinase signaling pathways is not significantly affected in CARMA1 KO B cells and not likely a reason for the defective proliferation.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Pharmacological inhibition of any of these pathways dramatically reduces the proliferation response induced by CD40 stimulation [37]. However, our data suggest that activation of these MAP kinase signaling pathways is not significantly affected in CARMA1 KO B cells and not likely a reason for the defective proliferation.…”
Section: Discussionmentioning
confidence: 52%
“…Proliferation of B cells upon CD40 stimulation requires NF-jB activation and NF-jBdependent induction genes such as cyclin-D2 [37,38]. However, our data indicated that activation of NF-jB is not defective in CD40-stimulated CARMA1 KO B cells (Fig.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Whether Ltb expression is up-regulated in later time points beyond 4 h is unknown. CD40L was previously shown to induce strong and sustained up-regulation of Ltb in B cells following 24 h of stimulation (61). It is possible that costimulation with CD40L is required to up-regulate Ltb in B cells during T-dependent immune response.…”
Section: Gene Expression Change Patterns Distinguishing Anti-igmentioning
confidence: 99%